2003
DOI: 10.1164/rccm.200209-1070oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Diaphragm Remodeling Associated with Chronic Obstructive Pulmonary Disease

Abstract: Diaphragm remodeling associated with chronic obstructive pulmonary disease (COPD) consists of a fast-to-slow fiber type transformation as well as adaptations within each fiber type. To try to explain disparate findings in the literature regarding the relationship between fiber type proportions and FEV1, we obtained costal diaphragm biopsies on 40 subjects whose FEV1 ranged from 118 to 16% of the predicted normal value. First, we noted that our exponential regression model indicated that changes in FEV1 can acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 28 publications
6
106
1
2
Order By: Relevance
“…Furthermore, the increase in type I fiber populations is clearly related to the severity of disease and the extent of hyperinflation, as shown in Fig. 2, C and D, from Levine et al (40).…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 55%
See 4 more Smart Citations
“…Furthermore, the increase in type I fiber populations is clearly related to the severity of disease and the extent of hyperinflation, as shown in Fig. 2, C and D, from Levine et al (40).…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 55%
“…The largest exceptions to this are the work of Lewis et al (43), who showed reductions in in vitro specific force of Ͼ20%, and Huenks et al (32), who demonstrated reductions of ϳ14%. In human studies of isolated fibers from biopsy specimens, two groups, Levine et al (40) and Ottenheijm et al (64), have found significant reductions in specific force in individual costal diaphragm fibers (Table 2), an observation recently confirmed in another group of COPD patients by these authors (86 1, increase; 2, decrease; TLC, total lung capacity; FRC, functional residual capacity;…”
Section: Changes In Specific Forcementioning
confidence: 83%
See 3 more Smart Citations